2021
DOI: 10.46939/j.sci.arts-21.4-b02
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization Using Quality by Design (Qbd) Approach of a Gentamicin Loaded Plga Biocomposite

Abstract: Osteomyelitis continues to be a major concern when orthopedic surgery is performed. Orthopedic infections have an incidence of 5% to 10% but their management proves to be quite difficult due to both biofilm formation and limited access of the drug to the infected area when systemic treatment is employed. The aim of the study was to optimize the synthesis process of a gentamicin loaded poly(-lactic-co-glycolic) acid (PLGA) based biodegradable composite by varying parameters that affect both efficiency encapsula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…We used PVA as a non-ionic surfactant [ 50 ] in the aqueous phase, which has hydrophilic head and a hydrophobic tail ([CH2CH(OH)]n), which is considered a critical double emulsion-stabilizing surfactant, although there are studies that consider that an increased concentration of it can affect the encapsulation efficiency [ 51 ]. Since in our previous studies of experimental design we found that the stirring speed had no major impact on efficiency or particle size, therapeutic agent encapsulation efficiency increases with concentration and pH, and decrease with PLGA concentration [ 52 , 53 ], we chose to investigate how other parameters influence the size of Zn–B–PLGA biocomposite, such as the amount of polymer added in the synthesis process and the concentration of the emulsifying agent. Our findings confirm that the size of the particles increases with increasing amounts of PLGA and PVA.…”
Section: Discussionmentioning
confidence: 99%
“…We used PVA as a non-ionic surfactant [ 50 ] in the aqueous phase, which has hydrophilic head and a hydrophobic tail ([CH2CH(OH)]n), which is considered a critical double emulsion-stabilizing surfactant, although there are studies that consider that an increased concentration of it can affect the encapsulation efficiency [ 51 ]. Since in our previous studies of experimental design we found that the stirring speed had no major impact on efficiency or particle size, therapeutic agent encapsulation efficiency increases with concentration and pH, and decrease with PLGA concentration [ 52 , 53 ], we chose to investigate how other parameters influence the size of Zn–B–PLGA biocomposite, such as the amount of polymer added in the synthesis process and the concentration of the emulsifying agent. Our findings confirm that the size of the particles increases with increasing amounts of PLGA and PVA.…”
Section: Discussionmentioning
confidence: 99%
“…We used PVA as a non-ionic surfactant [50] in the aqueous phase, which has hydrophilic head and a hydrophobic tail ([CH 2 CH(OH)] n ), which is considered a critical double emulsion-stabilizing surfactant, although there are studies that consider that an increased concentration of it can affect the encapsulation efficiency [51]. Since in our previous studies of experimental design we found that the stirring speed had no major impact on efficiency or particle size, therapeutic agent encapsulation efficiency increases with concentration and pH, and decrease with PLGA concentration [52,53], we chose to investigate how other parameters influence the size of Zn-B-PLGA biocomposite, such as the amount of polymer added in the synthesis process and the concentration of the emulsifying agent. Our findings confirm that the size of the particles increases with increasing amounts of PLGA and PVA.…”
Section:  Discussionmentioning
confidence: 99%